Integrated conodont and radiolarian biostratigraphy of the upper Norian in Baoshan Block, Southwestern China. (12th March 2020) - Du, Yixing; Bertinelli, Angela; Jin, Xin; Shi, Zhiqiang; Karádi, Viktor; Yin, He; Han, Lu; Wu, Qiangwang; Rigo, Manuel
Abstract : Two significant stratigraphical microfossils, conodonts and radiolarians, are usually used for the Upper Triassic chronostratigraphy. The Baoshan Block was located in eastern Tethys during the Late Triassic where the biostratigraphical data of Upper Triassic are still poorly known. We collected new samples from the Hongyan section (HY) for biostratigraphical study. This 24‐m‐thick section in Dabaozi Village, Baoshan City, is mainly composed of thin‐layered limestones, sandstone and siltstone. The conodont fauna is referred to Sevatian 1 (late Norian), in which the species Mockina englandi, Mockina carinata and Mockina mosheri morphotype B are first recognized in the Baoshan Block, and thus eastern Tethys. The Norian radiolarian associations are first reported in the Baoshan Block, which correlate with the biozonation of North America and also that proposed for Central Japan. The radiolarian assemblages found in the analysed samples in HY section can be referred to the Sevatian Betraccium deweveri Zone. The Baoshan Block is a key area for conodont and radiolarian‐based correlations between the Tethys, Japan and North American domains.